220k views
0 votes
Simplify.

−4x2−5(x+3)+x2

−4x2−5x−15

−3x2−5x−15

−9x2−15

−23x

User Changed
by
5.2k points

2 Answers

4 votes
−4x2−5(x+3)+x2= -8-5x-15+2x=-3x-23
−4x2−5x−15=-8x-5x-15=-13x-15
−3x2−5x−15=-6x-5x-15=-11x-15
−9x2−15=-18x-15
i simplified assuming it's an "x"-sign not multiplication
hope this helps
User Patstew
by
6.2k points
5 votes

Answer:

Option 2nd is correct


-3x^2-5x-15

Explanation:

The distributive property says that:


a \cdot (b+c) = a\cdot b+ a\cdot c

Given the equation:


-4x^2-5(x+3)+x^2

Combine like terms;


-3x^2-5(x+3)

Apply the distributive property we have;


-3x^2-5x-15

therefore, the simplified form for the given equation is:


-3x^2-5x-15

User Jim Jam
by
6.2k points